REORIENTASI PERAN HUKUM DALAM MENGHADAPI DISRUPSI TEKNOLOGI:STUDI NORMATIF TENTANG REGULASI DIGITAL DI INDONESIA - Bahram, Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Technological disruption has brought fundamental changes to various aspects of life, including Indonesia's legal system. Existing regulations are often reactive and unable to accommodate the rapid development of digital technologies such as artificial intelligence (AI), blockchain, and fintech. This study aims to analyze the challenges and adaptation strategies of the legal system in facing digital transformation. The research employs a normative juridical approach by analyzing legal regulations, academic literature, and case studies from various countries. The findings indicate that Indonesia's legal system still faces several challenges in implementing digital regulations, including limited institutional capacity, low public digital literacy, and regulatory overlaps among government agencies. Therefore, regulatory reforms must adopt a more flexible, principle-based approach and ensure harmonization among related institutions. In conclusion, Indonesia's legal system needs to adapt progressively to provide effective legal protection in the digital era without hindering technological innovation